KORUPSI DI PESANTREN; DISTORSI PERAN KIAI DALAM POLITIK - Rudy Haryanto (Institut Agama Islam Negeri Madura)
AbstractNowadays, there are many Kiai facing distorsi of kekiaiannya. Kiai tends to be politician now. It is difficult to look for a careful kiai if he is given an unclear thing of its purpose. Being careful in his action was a part of kiai’s consistency in the past to keep it to all people especially political party. In occasion of showing one sidedness to the religion norms and the society. Now some kiai openly become politician and involve in activity to support political activity. It means kiai coming to public area that is susceptible to corruption. Therefore, it gets difficulty to find a careful kiai in their action, hold the religion forms, and put their religious community forward. This kind of kiai have ‘keintiman’ with God, strong spiritual relationship with their society. Because of their kindness makes them not easy to be tempted by the power that tend to do corruption.Kata-kata kunciPesantren, Kiai politik, dan korupsi